Kurragömmasyntaxen: Det poetiska språkets grammatik i dikter av Ann Jäderlund - Blomqvist, Jim (Tidskrift för litteraturvetenskap, 2016)
Hide-and-Seek Syntax: The Grammar of Poetic Language in Ann Jäderlund’s Poetry In the initial stage of the so-called ”Jäderlund debate” of the late 1980s, literary critic Tommy Olofsson essentially characterized Ann Jäderlund’s poetry as meaningless. In response, Åsa Beckman claimed that Olofsson’s inability to understand Jäderlund’s poetry was due to his utter lack of insight into female experience. This difference of opinion proves the necessity of distinguishing between the poem as part of a literary convention and the poem as part of a sociocultural ontology: how a poem makes meaning is different from an interpretation of what it means. The purpose of this article is to analyze syntax and grammar in Jäderlund’s poetry. Jäderlund has been referred to as a ”difficult” poet; in part, due to her unconventional, and often ungram matical, use of language. Examined in terms of motifs and plot, the poems exhibit special syntactical categories with regard to the function and position of words within individual verse lines. The aim of this article is to show the central active constituents in an interpretation of poetic language. The objects of analysis are two poems from Jäderlund’s sixth collection, Kalender röd Levande av is (Calender Red Alive with Ice, 2000). This work was chosen in order to expand upon two previous analyses of this material: Staffan Bergsten’s, ”Ann Jäderlund’s Tranformation Poetics”, and Mikael van Reis’s, ”Ann Jäderlund’s Syntax”. The main analysis is preceded by a short discussion of key elements in Bergsten’s and van Reis’s texts, and a theoretical discussion of the principles of poetic language. The conclusion of the article connects my analysis to feminist research in order to show how the inner structure of the poem creates meaning within an ideological environment, and to show that social conflicts are activated in the aesthetic structure of the poems.